Power and Self Image through Transitivity and Modality: Systemic Functional Linguistic Approach - Chalimah, Chalimah; Sumarlam, Sumarlam (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Abstract: The aim of this research was to investigate the transitivity and the modality used by the president of Indonesia âJokowiâ. I wanted to find out the power and the image of the president through the analysis of his utterances and answered the relation between social and context. I analyzed two speeches. I took the speech texts from Rappler.com. It was an online news site. I analyzed the data by using Hallidayâs theory of Systemic Functional Linguistics. There were three findings in this research namely: 1) the word âsayâ as the verbal process could be also as the example for behavioral process but it needed more explanation that it was verbal in action; 2) The most common process types used by Jokowi were material process, relational process, and mental process. 3) The biggest part of speech 1 and speech 2 were in the level of median politeness.